The Practice of Mindfulness of Kaya Satipatthana - Mahavong, Thonglon (BUDDHO, 2023)
The practice of mindfulness of the body (Kaya Satipatthana) is a fundamental aspect of Buddhist meditation aimed at cultivating mindfulness (sati) and wisdom (panna). This practice involves maintaining awareness of the body as it truly is, through techniques such as mindfulness of breathing (Anapanasati), awareness of bodily postures (Iriyapatha 4), clear comprehension (Sampajanna), contemplation of bodily unattractiveness (Patikulamanasikara), and contemplation of the four elements (Dhatu Manasikara). These methods help practitioners achieve mental tranquility, reduce distractions, and develop insight into impermanence (anicca), suffering (dukkha), and non-self (anatta). Ultimately, the practice leads to a more peaceful and joyful life and can be applied effectively in daily living beyond the traditional religious context.